Numerical study on the performance of combined Darrirus-Savonius vertical axis wind turbine - Khammas, Farhan A.; Nabil, Rand (Edelweiss Applied Science and Technology, 2025)
CFD simulations were conducted for these types of wind rotors to address the increasing focus of scholars in the renewable energy sector on studying the adoption of sustainable energy sources and reducing fossil fuel consumption. Vertical axis wind turbines (VAWTs) have become increasingly prevalent for wind power generation. This work presents a computational analysis of the performance of a vertical-axis wind turbine for three designs using Fluent 2020 R2 CFD software. The three designs’ three-dimensional computational fluid dynamics (CFD) were compared using the k-epsilon augmented wall treatment as a turbulence model at an airflow velocity of 5 m/s. From this study, it can be concluded that it is possible to use this type of hybrid wind turbine in areas with low wind speeds due to their quick response to rotation. For these reasons, this type of hybrid wind turbine can be used in residential areas as a practical application, since these areas are characterized by low wind speeds in most cases.